Extracellular Tannase from Aspergillus ochraceus: Influence of the Culture Conditions on Biofilm Formation, Enzyme Production, and Application - Aracri, Fernanda Mansano [UNESP]; Farias Cavalcanti, Rayza Morganna [UNESP]; Souza Guimaraes, Luis Henrique (Korean Soc Microbiology & Biotechnology, 2019)
Aspergillus ochraceus biofilm, developed on an inert support, can produce tannase in Khanna medium containing 1.5% (w/v) tannic acid as the carbon source, at an initial pH of 5.0, for 72 h at 28 degrees C. Addition of 0.1% (w/v) yeast extract increased enzyme production. The enzyme in the crude filtrate exhibited the highest activity at 30 degrees C and pH 6.0. At 50 degrees C, the half-life was 60 min and 260 min at pH 6.0. In general, addition of detergents and surfactants did not affect tannase activity significantly. Tannase has potential applications in various biotechnological processes such as the production of propyl gallate and in the treatment of tannin-rich effluents. The content of tannins and total phenolic compounds in effluents from leather treatment was reduced by 56-83% and 47-64%, respectively, after 2 h of enzyme treatment. The content of tannins and total phenolic compounds in the sorghum flour treated for 120 h with tannase were reduced by 61% and 17%, respectively. Interestingly, the same A. ochraceus biofilm was able to produce tannase for three sequential fermentative process. In conclusion, fungal biofilm is an interesting alternative to produce high levels of tannase with biotechnological potential to be applied in different industrial sectors.
Keywords: Biofilm fermentation; fungal biofilm; leather effluent; tannase; tannin acyl hydrolase